A sluggish demand could be as potent as technological progress in creating surplus in staple production: the case of Bangladesh - Ahmed, Raisuddin (International Food Policy Research Institute, 1997)
During the decade from 1982/83 through 1992/93, Bangladesh was able to increase production of rice, its staple food, at a rate modestly higher than the growth in population. However, the growth in per capita supply remained stagnant, because of the substitution of imports with domestic production. On the other hand, per capita income grew about 2 percent per annum. Nevertheless, the real price of rice declined about 2.7 percent annually. This decline in the rice price, on the face of a stagnant supply and increasing incomes, aroused suspicion whether income distribution has twisted against the poor who have a higher marginal propensity to consume rice compared to the rich. Three factors are identified that contributed to the decline in the rice price while per capita income increased: a) urbanization, b) diversification of diet, and c) income distribution. The analysis shows that, of a total demand depressing effect of 15.6 percent, urbanization accounts for 4 percentage points, cross-price effects for 7 percentage points, and worsening income distribution accounts, residually, for 4.6 percentage points. These findings are based on plausible values of demand and supply parameters which warrant fresh evaluation in the context of rapid structural change in the economy of Bangladesh.